Malformación arterial pura: revisión de la literatura y presentación de un caso - Gonzalez Dutra, Maria Laura; Oneto, Alejandro; Bozzetti, Carlos; Requejo, Flavio (Revista Argentina de Neurocirugía, 2022)
-